Atividade antiedema do pró-fármaco polimérico PDC-70 derivado do diclofenaco - Nassute, José Carlos [UNESP]; Longo, Maria do Carmo [UNESP]; Menegon, Renato Farina; Ribeiro, Yoko Asakura; Chin, Chung Man [UNESP] (My University, 2002)
The PDC-70 polymeric prodrug derived from the diclofenac has shown antiedema activity when administered through intramuscular route in rats. Besides that it has produced superior activity when compared to the diclofenac sodium. These promising results indicate antiinflammatory activity for the PDC-70 polymeric prodrug.
Antiedema activity of the PDC-70 polymeric prodrug derived from the diclofenac
Keywords: Antiedema; Antiinflamatory; Diclofenac; Latentation; Prodrug; antiinflammatory agent; diclofenac; diclofenac derivative; pdc 70; prodrug; unclassified drug; animal experiment; antiinflammatory activity; controlled study; edema; nonhuman; time series analysis